It's Not Just Dinner: Meal Delivery Kits as Food Media for Food Citizens - Khan, Sabiha Ahmad; Sowards, Stacey K. (Frontiers in Communication, 2018)
Meal kit delivery services rhetorically appeal to middle class consumers who have busy lives, but want to eat good quality food without the hassle of grocery shopping and meal planning. In this paper, we advance three arguments to explore the cultural phenomenon of these meal services that are growing exponentially across the United States and in other countries. First, such meal kits, in their efforts to provide meal and ingredient variation, decontextualize food cultures while promoting a consumer sense of cosmopolitanism. Second, meal kit companies have attempted to address environmental concerns of waste production, but many of those problems have yet to be resolved despite rhetorical appeals to the contrary. Finally, while such meal kits do not address fully the challenges and problems of global food production and capitalist systems, they do confront those who use them with some of the realities of where their food comes from and what kind of waste it produces. We ultimately argue that such companies manifest the return of the repressed through the material and rhetorical production of food and waste even as they employ diverse cultural food options and erase those cultural origins at the same time. Meal kit delivery services’ interactivity and confrontation with waste distinguishes them from traditional food media. Despite their investment in the performative dimensions of cooking as a way to reconnect with the food system, they also miss opportunities to address gender, culture, and waste that limits the radical potential of that performativity.